KEKAYAAN JENIS LANDAK LAUT (ECHINOIDEA) FAMILI DIADEMATIDE DI PANTAI SELATAN KABUPATEN GUNUNG KIDUL - Purnami, S.E.; Trijoko, Trijoko; Rarastoeti, Pratiwi (Sains & Matematika, 2012)
Diadematidae is one of sea urchin families belongs to Class Echinoidea that can be found in intertidal zone untill deep sea. These sea urchins have long spines, and some of them are toxic spines. However, they have important ecological roles. This research aimed to identify the species richness of sea urchins that belong to Family Diadematidae in Pantai Selatan Gunung Kidul as well as describe their taxonomic characters. Specimens were collected from five beaches, namely Krakal, Kukup, Drini, Sepanjang, and Wediombo. Collected specimens were relaxated by using MgCl272% in sea water and the fixed by using 10% formalin in sea water. Finally, they were preserved in 70% Ethanol. Some morphological characters were observed carefully, namely shape and colour of spines, shape of test, shape of genital plate, the existance of orange ring, white spot and iridipore of apical system, interambulacral region, and number of pores. The results showed that there were five species of Diadematid sea urchis in Pantai Selatan Yogyakarta; they belong to two genus, namely genus Diadema dan genus Echinotrix. Genus Echinotrix and Diadema can be fount in Kukup, Wediombo, and Sepanjang, but can not be found in two others beach.